Security Issues in the Cloud Computing Environment : An Overview - Rajalakshmi, S (International Journal of Computer Sciences and Engineering, 2025)
In Cloud Computing environment, Security issues is the hottest topic. Many tools and techniques are applied to secure the data in the cloud server. Although, the security providers focus on data storage of third party at risk to be maintain sensitive information. As the information grows day by day, Security control over the data should be more effective and adaptive to changing risk services. Protection of data manages how data is stored, how it is accessed and how it is handled. Taking lease of many servers and provisioning the resources for usage cost turns to a revolution. This paper reveals the outline of cloud computing, cloud security concepts, challenges and solutions for dynamically securing sensitive data of unlimited resources and services.